Pengaruh Terapi Dingin Ice Massage terhadap Penurunan Skala Nyeri pada Petani Penderita Low Back Pain (LBP) di Desa Woerahi Kecamatan Meluhu Kabupaten Konawe Tahun 2016 - Tridaranto, I Nyoman; Said, Asbath (Jurnal Gizi Ilmiah, 2016)
Data obtained from Ahuhu Health Center in 2013 with Low Back Pain (LBP) as many as 12 patients and 17 patients in 2014, and 22 patients in 2015. This study aims to determine the effect of ice massage cold therapy on reducing pain scale in farmers with Low Back Pain. Back Pain (LBP) in Woerahi Village, Meluhu District, Konawe Regency in 2016. This type of research is a pre-experimental quantitative research with a one group pretest posttest design. The population in this study was 22 respondents. Sampling with saturated sampling technique or total sampling. The number of samples in this study were 22 respondents. The method of analysis used statistical analysis of the Wilcoxon Signed Ranks Test. The results of this study showed a decrease in pain scale before and after therapy. This can be seen from the statistical test value of the influence of cold ice massage therapy ( = 0.000) where < 0.05 then Ho is rejected and it can be concluded that there is a significant effect of cold therapy ice massage on reducing pain scale in patients with Low Back Pain ( LBP). Based on the results of this study, it is hoped that cold therapy ice massage can be an alternative in overcoming pain in patients with Low Back Pain (LBP).